Korelasi Antara Derajat Beratnya Osteoarthritis Lutut dan Cartilage Oligomeric Matrix Protein Serum - Andriyasa, Ketut; Putra, Tjokorda Raka (PAPDI BALI, 2017)
Prevalence of knee Oateoarthritis (OA) in the community is quite high.  Various attempts have been made to find markers of cartilage damage. One potential marker is Cartilage Oligomerix Matrix Protein (COMP). Based on this, researchers want to know whether there is a correlation between the severities of knee OA with serum concentration of COMP in human. This study is a cross sectional analytic study. The diagnosis of knee OA based on ACR criteria and the degree of knee OA severity is determined based on the Kellgren and Lawrance criteria. COMP patients are checked by using ELISA method. The correlation between the severities of knee OA and serum COMP was analyzed by Spearman correlation test. Level of statistical significance used was p < 0.05. Sixty-six patients included in this study, in which 28 (42,4%) of them were male and 38 (57,6%) were women. The mean age is 63,9 Â± 7.0 years with a range of 50 to 84 years. The severity of knee OA are :  4.5% for grade one, 35.8% grade two, 38.8% grade three and 20.9% at grade 4. The mean serum COMP concentration is 1084,0 ng / mL with range from 575.3 ng / mL to 2278,6 ng/mL. There is a trend of increasingly grade of severity of knee OA, the higher the concentration of serum COMP, but not statistically significant (r = 0.127, p = 0.31). In conclusion, there is no positif correlation that statistically significant between severity of knee OA and  serum COMP concentration.